Estimating the effect of pretreatment loss to follow up on TB associated mortality at public health facilities in Uganda - Zawedde-Muyanja, Stella; Musaazi, Joseph; Manabe, Yukari C.; Katamba, Achilles; Nankabirwa, Joaniter I.; Castelnuovo, Barbara; Cattamanchi, Adithya (PLoS ONE, 2020)
Tuberculosis (TB) mortality estimates derived only from cohorts of patients initiated on TB treatment do not consider outcomes of patients with pretreatment loss to follow-up (LFU). We aimed to assess the effect of pretreatment LFU on TB-associated mortality in the six months following TB diagnosis at public health facilities in Uganda. Methods At ten public health facilities, we retrospectively reviewed treatment data for all patients with a positive Xpert®MTB/RIF test result from January to June 2018. Pretreatment LFU was defined as not initiating TB treatment within two weeks of a positive test. We traced patients with pretreatment LFU to ascertain their vital status. We performed Kaplan Meier survival analysis to compare the cumulative incidence of mortality, six months after diagnosis among patients who did and did not experience pretreatment LFU. We also determined the health facility level estimates of TB associated mortality before and after incorporating deaths prior to treatment initiation among patients who experienced pretreatment LFU. Results Of 510 patients with positive test, 100 (19.6%) experienced pretreatment LFU. Of these, we ascertained the vital status of 49 patients. In the six months following TB diagnosis, mortality was higher among patients who experienced pretreatment LFU 48.1/1000py vs 22.9/ 1000py. Hazard ratio [HR] 3.18, 95% confidence interval [CI] (1.61–6.30). After incorporating deaths prior to treatment initation among patients who experienced pretreatment LFU, health facility level estimates of TB associated mortality increased from 8.4% (95% CI 6.1%- 11.6%) to 10.2% (95% CI 7.7%-13.4%). Conclusion Patients with confirmed TB who experience pretreatment LFU have high mortality within the first six months. Efforts should be made to prioritise linkage to treatment for this group of patients. Deaths that occur prior to treatment initation should be included when reporting TB mortality in order to more accurately reflect the health impact of TB.
Keywords: Pretreatment loss; TB associated mortality; Public health facilities